A Baseline Model For Estimating the Risk of Gas Embolism in Sea Turtles During Routine Dives - Robinson, Nathan J.; García-Párraga, Daniel; Stacy, Brian A.; Costidis, Alexander M.; Blanco, Gabriela S.; Clyde-Brockway, Chelsea E.; Haas, Heather L.; Harms, Craig A.; Patel, Samir H.; Stacy, Nicole I.; Fahlman, Andreas (Frontiers in Physiology, 2021)
Sea turtles, like other air-breathing diving vertebrates, commonly experience significant gas embolism (GE) after being incidentally caught in fishing gear and brought to the surface. To better understand why sea turtles develop GE, we built a mathematical model to estimate partial pressures of N2 (PN2), O2 (PO2), and CO2 (PCO2) in the major body-compartments of diving loggerheads (Caretta caretta), leatherbacks (Dermochelys coriacea), and green turtles (Chelonia mydas). This model was adapted from a previously published model for estimating the gas dynamics in marine mammals and penguins. To parameterize the model for sea turtle anatomy and physiology, we used a combination of values gleaned from previously published literature as well as 22 necropsies to assess the volume of different body compartments in the 3 species. Next, we applied this model to data collected from free-roaming individuals of the three study species. Finally, we varied both the body-condition and cardiac output within the model to see how these factors affected the risk of gas embolism (GE). Our model suggests that cardiac output likely plays a significant role in the modulation of GE, especially in the deeper diving leatherback turtles. This baseline model also suggests that sea turtles appear to be at high risk of GE even during routine diving behavior. This likely indicates that turtles have additional behavioral, anatomical, and/or physiologic adaptions, which were not incorporated in this model, that serve to reduce the probability of GE. Identifying these adaptations and incorporating them into future iterations of this original model will further reveal the factors driving GE in sea turtles.